Production Protocol Standardisation, Macroscopic and Histological Evaluation, and Growth Factor Quantification of Canine Leukocyte-and Platelet-Rich Fibrin Membranes - Caterino, Chiara; Della Valle, Giovanni; Aragosa, Federica; De Biase, Davide; Ferrara, Gianmarco; Lamagna, Francesco; Fatone, Gerardo (Frontiers in Veterinary Science, 2022)
Leukocyte-Platelet-Rich Fibrin (L-PRF) is a second generation of platelet concentrates; it was widely used, as an autologous platelet-based wound sealant and hemostatic agent in surgical wound healing. L-PRF clot or membrane is a solid fibrin-based biomaterial, with a specific 3D distribution of the leukocytes and platelet aggregates. This biological scaffold releases growth factors (i.e., TGF- β1, PDGF-AB, VEGF) and matrix proteins (fibronectin, vitronectin and thrombospondin-1) during the healing process after the application. To the Authors' knowledge both in human and veterinary medicine a single standardised protocol was not reported. This prospective study aimed to apply Crisci's L-PRF protocol (which is characterised by 30” of acceleration, 2' at 2,700 rpm, 4' at 2,400 rpm, 3' at 3,000 rpm, and 36” of deceleration and arrest) sin canine species, evaluate macroscopically and histologically the L-PRF membranes obtained by using Wound Box to standardise the L-PRF protocol in dogs and to evaluate the clinical feasibility of using L-PRF membranes by quantitative in vitro analysis of growth factors over 7 days. One hundred twenty-eight dogs in good general condition with no history of recent NSAIDs intake (15 days of washout) and/or any medication or disease related to coagulation process met inclusion criteria and therefore were enrolled. We obtained 172 membrane L-PRF membranes by 86 dogs: half of them underwent macroscopic and histological analysis, the other 86 underwent ELISA analysis. The Wound Box gave a membrane of mean (±SD) length (cm), width (cm) and weight (g) of 1.97 (±0.89), 0.95 (±0.36), 0.46 (±0.20) respectively. Histology analysis confirmed a well-defined histoarchitecture with five layers reproducing density and distribution of blood cells in this biomaterial. Finally, the ELISA assay performed with 22 L-PRF membranes showed a peak in growth factors at 6 h after membrane production, followed by a decrease in release at 24 and 72 h and a second peak in release at 168 h after production. Statistical analysis of demographic variables (age, sex, and body condition score BCS) and the average of growth factors determined by the ELISA assay did not reveal statistical significance, except for the BCS factor compared with the production of VEGF. Our data confirm the effectiveness of this protocol and of Wound Box to produce L-PRF membranes in dogs.